Buyer and non buyer of counterfeits of luxury brands: examining their differences in behavioural outcomes - Teah, Min (School of Marketing, Curtin Business School, 2009)
The purpose of the study is to examine the behavioural differences between non-buyer and buyer of counterfeits of luxury brands. Data was collected using a mall intercept in downtown Shanghai, China. 202 useable responses were retained for analysis. Findings revealed that there are differences between both group of consumers. Social and personality factors do influence attitudes and purchase intentions towards counterfeits of luxury brands. Managerial implications were also discussed.